Discrimination of Alismatis Rhizoma based on chromatographic fingerprint, multiple components quantification, and pattern recognition analysis. Issue 19 (13th December 2016) - Yu, Jingyi; Ma, Xueyang; Wang, Jun; Liang, Hong; Zhang, Qingying; Chen, Shizhong; Tu, Pengfei
ABSTRACT: A simple, sensible, and reliable HPLC–DAD method was first developed for fingerprint analysis of Alismatis Rhizoma, and then applied to analyze 85 samples from three main cultivated areas. In all, 40 common fingerprint peaks were designated, and six of which were definitely identified. Then, the combinatory analysis using similarity evaluation, principal component analysis, and orthogonal partial least square discriminant analysis revealed clear chemical consistency between samples from Fujian and Jiangxi provinces and substantial differences between those from Fujian/Jiangxi and Sichuan provinces. Furthermore, six components were dug out as potential chemical markers for distinguishing Alismatis Rhizoma from different areas, among which five were qualified for quantitative analysis. In conclusion, the combination of chemical fingerprint, multiple components quantification, and pattern recognition analysis was rather powerful and useful in discriminating Alismatis Rhizoma from different regions, which was a benefit for quality control. GRAPHICAL ABSTRACT: